A case report of broken tip of thrombus aspiration catheter (Thrombuster II) in ectatic left circumflex artery of young patient with Kawasaki disease. Issue 1 (26th February 2020) - Oo, Mon M; Ismail, Muhammad DB; Abidin, Imran Z; Ahmad, Wan AW
No abstract available